2022
DOI: 10.1177/17474930221099352
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of cognitive impairment in cerebral amyloid angiopathy

Abstract: Background Cerebral amyloid angiopathy (CAA) is associated with cognitive decline. CAA has diverse impacts on brain structure and function; however, the brain lesions that mediate the association of CAA with cognition are not understood well. Aims To determine the degree to which CAA neuroimaging biomarkers mediate the association of CAA with cognitive dysfunction. Methods We analyzed cross-sectional data of patients with probable CAA and controls without cognitive impairment from the Functional Assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 22 publications
1
17
1
Order By: Relevance
“…A paper by Durrani in this month issue reports that altered white matter diffusivity, cerebrovascular reactivity, and atrophy, taken together, accounted for about half the effect of CAA on cognition. 9 While we have considerable data on risk factors for SVD itself, there are limited data on what are the risk factors for cognitive impairment in patients with SVD. A paper by Ohlmeier et al 35 also in this issue in almost 1000 lacunar stroke patients reports that diabetes mellitus (odds ratio (OR) = 1.98, 95% CI = (1.40-2.80), p < 0.001) and higher body mass index (BMI) (OR = 1.03, 95% CI = (1.00-1.05), p = 0.029) were independently associated with increased risk of VCI and years of full-time education with lower risk (OR = 0.92, 95% CI = (0.86-0.99), p = 0.018).…”
Section: Svd and Cognitive Impairmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A paper by Durrani in this month issue reports that altered white matter diffusivity, cerebrovascular reactivity, and atrophy, taken together, accounted for about half the effect of CAA on cognition. 9 While we have considerable data on risk factors for SVD itself, there are limited data on what are the risk factors for cognitive impairment in patients with SVD. A paper by Ohlmeier et al 35 also in this issue in almost 1000 lacunar stroke patients reports that diabetes mellitus (odds ratio (OR) = 1.98, 95% CI = (1.40-2.80), p < 0.001) and higher body mass index (BMI) (OR = 1.03, 95% CI = (1.00-1.05), p = 0.029) were independently associated with increased risk of VCI and years of full-time education with lower risk (OR = 0.92, 95% CI = (0.86-0.99), p = 0.018).…”
Section: Svd and Cognitive Impairmentmentioning
confidence: 99%
“…CAA is the primary cause of lobar ICH and an independent contributor to age-associated cognitive impairment. 8 10 …”
Section: Etiology—the Heterogeneity Of Svdmentioning
confidence: 99%
“…10 In patients with SVD, caused by both hypertension and CAA, a key mechanism appears to be disruption of white matter pathways underlying complex cortical-subcortical networks, which can be interrupted by the diverse pathologies occurring in SVD, including lacunar infarcts, white matter hyperintensities, more diffuse white matter damage seen on DTI, and cerebral microbleeds. 11,12 Such imaging markers are providing important…”
mentioning
confidence: 99%
“…More recent studies, however, have failed to detect a significant association between WMHV and cognitive impairment in CAA. 53,93 1.2.5.1.5. Lobar lacunes Lacunes of presumed vascular origin represent cavities filled with fluid in the white matter or deep gray matter, that substitute tissue destroyed by ischemic or hemorrhagic injury, and are surrounded by reactive astrocytes, myelin and axonal loss, with significant perilesional tissue disruption.…”
Section: Css/sahmentioning
confidence: 99%
“…112 A recent case-control study observed that, alongside CVR and a DWIbased marker, atrophy mediated the effect of CAA on cognition. 93 In a study comprising 158 non-demented probable CAA patients, medial temporal atrophy independently predicted conversion to dementia, indicating that there is likely a contributing role of AD pathology. 53 In a case-control study with 58 non-demented CAA patients and 138 cognitively normal controls, TBV was the only neuroimaging marker associated with executive function and processing speed.…”
Section: Atrophymentioning
confidence: 99%